2020
DOI: 10.1021/acs.chemmater.0c02746
|View full text |Cite
|
Sign up to set email alerts
|

Extending Afterglow of Ga2O3 Nanocrystals by Dy3+ Dopant-Induced Carrier Trapping: Toward Design of Persistent Colloidal Nanophosphors

Abstract: Design and preparation of persistently luminescent nanostructured phosphors are of a significant interest in lighting, photonic, and photovoltaic technologies. However, afterglow generally occurs in bulk phosphors synthesized by high-temperature solid-state reactions. Here, we report the synthesis of colloidal Dy 3+doped γ-phase Ga 2 O 3 nanocrystals and demonstrate an extension of the lifetime of nanocrystal emission arising from native-defect-based donor−acceptor pair recombination, relative to undoped nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…As reported, assisting with suitable co‐dopants is one of the most efficient methods to optimize both the intensity and afterglow time of the afterglow. It is a universal method for all kinds of persistent phosphors, for instance, SrAl 2 O 4 :Eu 2+ ,Dy 3+ , [ 35 ] CaAl 2 O 4 :Eu 2+ ,Nd 3+ ,Gd 3+ , [ 41a,148 ] BaSiO 3 :Eu 2+ ,Nd 3+ ,Tm 3+ , [ 72 ] ZnGa 2 O 4 :Cr 3+ ,Gd 3+ , [ 95c ] Zn 2.94 Ga 1.96 Ge 2 O 10 :Cr 3+ ,Pr 3+ , [ 25b ] Zn 1.25 Ga 1.5 Ge 0.25 O 4 :Cr 3+ ,Yb 3+ ,Er 3+ , [ 149 ] MgGeO 3 :Mn 2+ ,Yb 3+ , [ 123 ] Mg 2 GeO 4 :Mn 2+ ,Yb 3+ , [ 121 ] CdSiO 3 :Bi 3+ ,Gd 3+ , [ 105a ] Y 2 O 2 S:Eu 3+ ,Mg 2+ ,Ti 4+ , [ 150 ] La 3 Ga 5 GeO 14 :Cr 3+ ,Zn 2+ , [ 151 ] ZnGa 2 O 4 :Cr 3+ ,Bi 3+ , [ 90a ] Ca 0.85 Zn 0.15 TiO 3 :Pr,B, [ 152 ] Ga 2 O 3 :Dy 3+ , [ 153 ] and Zn 2 GeO 4 :Mn,Li,K. [ 99b ]…”
Section: Dopant/host Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…As reported, assisting with suitable co‐dopants is one of the most efficient methods to optimize both the intensity and afterglow time of the afterglow. It is a universal method for all kinds of persistent phosphors, for instance, SrAl 2 O 4 :Eu 2+ ,Dy 3+ , [ 35 ] CaAl 2 O 4 :Eu 2+ ,Nd 3+ ,Gd 3+ , [ 41a,148 ] BaSiO 3 :Eu 2+ ,Nd 3+ ,Tm 3+ , [ 72 ] ZnGa 2 O 4 :Cr 3+ ,Gd 3+ , [ 95c ] Zn 2.94 Ga 1.96 Ge 2 O 10 :Cr 3+ ,Pr 3+ , [ 25b ] Zn 1.25 Ga 1.5 Ge 0.25 O 4 :Cr 3+ ,Yb 3+ ,Er 3+ , [ 149 ] MgGeO 3 :Mn 2+ ,Yb 3+ , [ 123 ] Mg 2 GeO 4 :Mn 2+ ,Yb 3+ , [ 121 ] CdSiO 3 :Bi 3+ ,Gd 3+ , [ 105a ] Y 2 O 2 S:Eu 3+ ,Mg 2+ ,Ti 4+ , [ 150 ] La 3 Ga 5 GeO 14 :Cr 3+ ,Zn 2+ , [ 151 ] ZnGa 2 O 4 :Cr 3+ ,Bi 3+ , [ 90a ] Ca 0.85 Zn 0.15 TiO 3 :Pr,B, [ 152 ] Ga 2 O 3 :Dy 3+ , [ 153 ] and Zn 2 GeO 4 :Mn,Li,K. [ 99b ]…”
Section: Dopant/host Selection Criteriamentioning
confidence: 99%
“…In contrast, 580 nm ( 4 F 9/2 → 6 H 13/2 ) yellow emission originating from hypersensitive forced electric dipole transition will be impacted by the surrounding environment significantly. [ 68a–c,153,219 ] Thereby, dominant yellow luminescence will be produced by Dy 3+ in local site with low symmetry and without inversion symmetry, conversely, dominant blue luminescence will be generated. Chen et al reported the varied color of Dy 3+ in different hosts of Ca x MgSi 2 O 5+ x :Dy 3+ ( x = 1, 2, 3).…”
Section: Multi‐color Persistent Luminescencementioning
confidence: 99%
“…Matsuzawa et al . first reported aluminates green PLNPs (SrAl 2 O 4 :Eu 3+ , Dy 3+ ) in 1996, [4] PLNPs attracted tremendous attention in various fields such as night lighting, national defense and military, optical storage, chemistry, materials, and biomedical sciences [5–11] . To date, various PLNPs matrixes were developed, e. g ., silicate, gallate, and Ga 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Gallate matrix PLNPs attracted increasing interest in the presence of spinel structure, small bandgap energy difference, and stable chemical properties, [1] while they are still fundamentally plagued with poor fluorescence quantum efficiency, short persistent luminescence time, large particle size, poor water solubility, and low biocompatibility, [12] which greatly hinders their applications. Ga 2 O 3 matrix PLNPs have a wide band‐gap of 4.9 eV and contained native defects as the persistent luminescence activators that can be controlled via reaction conditions, and the dopants responsible for energy storage need to be externally introduced to design longer‐lasting nanophosphors based on Ga 2 O 3 [4,13–14] …”
Section: Introductionmentioning
confidence: 99%
“…With regard to its optical properties, β-Ga 2 O 3 is almost transparent, and β-Ga 2 O 3 nanoparticles have been demonstrated to exhibit photoluminescence upon doping. [8][9][10][11][12][13][14][15][16][17] In addition to these applications, β-Ga 2 O 3 has potential use in catalysis, 18,19 solar cells, 20 and gas sensors. 21 β-Ga 2 O 3 nanoparticles are also used as precursors in the synthesis of GaN nanoparticles via the nitration process.…”
Section: Introductionmentioning
confidence: 99%